2012
DOI: 10.1007/s10792-012-9572-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of anisometropic amblyopia on retrobulbar blood flow parameters

Abstract: To look for a correlation between or the effect of anisometropia amblyopia on retrobulbar blood flow parameters. Peak systolic velocity (PSV) and end-diastolic velocity (EDV) of the ophthalmic artery (OA), central retinal artery (CRA), and temporal posterior ciliary artery (tPCA) were measured with color Doppler imaging, and systolic/diastolic ratio, resistivity index (RI), and pulsatility index (PI) were computed in 42 patients with anisometropic amblyopia. The mean PSV of OA, CRA, and tPCA in amblyopic and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In humans with amblyopia, with low temporal frequency visual stimuli, cerebral blood flow has been shown to be decreased in contralateral visual cortex (7). In a study examining effects of anisometropic amblyopia on retrobulbar blood flow with color Doppler imaging, no changes were detected in flow parameters of the ophthalmic artery, central retinal artery, or temporal posterior ciliary artery (8).…”
Section: Introductionmentioning
confidence: 99%
“…In humans with amblyopia, with low temporal frequency visual stimuli, cerebral blood flow has been shown to be decreased in contralateral visual cortex (7). In a study examining effects of anisometropic amblyopia on retrobulbar blood flow with color Doppler imaging, no changes were detected in flow parameters of the ophthalmic artery, central retinal artery, or temporal posterior ciliary artery (8).…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistically significant difference in retrobulbar blood flow between the amblyopic eye and the healthy eye in patients with anisometropic amblyopia [23]. The larger number of patients in our study is more significant in terms of literature.…”
Section: Discussionmentioning
confidence: 49%
“…The amacrine synapses found within the IPL of amblyopic eyes were increased [26]. In light of histological [10,19,[23][24][25] and OCT studies that supported the presence of retinal morphological abnormalities [3][4][5][6][7][8], we expected to find significant changes in the mean reflectivity of AE. We hypothesized to see a decrease in the RNFL (ROI#8) and GCL (ROI#7 and 9), and a change in the average intensity of IPL (ROI#7 and 10).…”
Section: Plos Onementioning
confidence: 84%
“…As for the retina, previous histologic studies in amblyopic animal models have demonstrated atrophy in optic nerve fibers and a decrease in retinal ganglion cells' density and size [19,23,24], in addition to a decrease in their nucleolar volume [25]. The amacrine synapses found within the IPL of amblyopic eyes were increased [26].…”
Section: Plos Onementioning
confidence: 89%
See 1 more Smart Citation